Feeding blood meal to Sudan desert sheep. I. Effect on feedlot performance and carcass characteristics of lambs - Mansour, M.E.; Tibin, I.M.; El Tayeb, A.E.; Sulieman, A.H. (1988)
Ths report examines the effect of different levels of blood meal on feedlot performance and carcass characteristics of Sudan Desert Sheep. It discusses data on feed intake, weight gain and feed efficiency.